Edukasi dan Sosialisasi Kegiatan Vaksinasi Covid-19 Pada Masyarakat Desa Sukaindah Sebagai Upaya Dalam Mendukung Gerakan Berani (Bekasi Berantas Pandemi) Tahun 2021 - Adinda Ayu R; Arasya Zahra Mawaddah; Salsabila Alia Syifa Ibrahim; Anom Dwi Prakoso (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM Universitas Respati Indonesia), 2023)
The initial emergence of the Covid-19 virus sparked various responses from the community of Sukaindah Village. Fear of illness and death due to Covid-19 vaccination in Sukaindah Village significantly escalated. The presence of hoax news circulating among the community regarding deaths from vaccination further fueled fear among the residents of Sukaindah Village. As an effort to alleviate the anxiety of the community in Sukaindah Village, various measures are required to enhance the optimism of the people amidst this pandemic. For individuals who are afraid of being vaccinated, the involvement of healthcare personnel and surrounding stakeholders is necessary to provide education and socialization about Covid-19 vaccination activities to the residents of Sukaindah Village, as part of the effort to support the Bold Movement (Bekasi Fights Pandemic). This Community Service Progam (KKN) conducted by Suherman Medika University students in Sukaindah Village, Sukakarya District, Bekasi Regency. This activity was carried out within a period of 10 days, start from September 13 to September 24, 2021. The existence of hoax circulating among the public about deaths due to vaccinations scared the residents of Sukaindah Village. Focus of community service is data collection on vaccines, education and socialization to accelerate the increase in vaccination achievements, especially in Sukaindah Village. The results of the KKN-T evaluation showed an increase in public understanding of 76% and an increase in vaccination achievement by 3% within a period of 10 days. Keywords: education, socialization, vaccination, bekasi regency program to eradicate the pandemic